Answer:
(x) = 6 - 4x
Step-by-step explanation:
let y = f(x) and rearrange making x the subject
y = -
x +
( multiply through by 4 to clear the fractions )
4y = - x + 6 ( subtract 6 from both sides )
4y - 6 = - x ( multiply through by - 1 )
- 4y + 6 = x
Change y back into terms of x with x =
(x) , then
(x) = 6 - 4x
The question that you have input is clearly wrong. It's not a quardratic equation. 10X2 doesn't make any sense for a quadratic equation. You should change it to 10x^2 which would make more sense
(x–4) (3x^2 + 2)
i hope that helps with you’re expression
Answer:
-14n - 2r - 21
Step-by-step explanation:
Answer:
The function y = sec(x) shifted 3 units left and 7 units down .
Step-by-step explanation:
Given the function: y = sec(x)
- If k is any positive real number, then the graph of f(x) - k is the graph of y = f(x) shifted downward k units.
- If p is a positive real number, then the graph of f(x+p) is the graph of y=f(x) shifted to the left p units.
The function
comes from the base function y= sec(x).
Since 3 is added added on the inside, this is a horizontal shift Left 3 unit, and since 7 is subtracted on the outside, this is a vertical shift down 7 units.
Therefore, the transformation on the given function is shifted 3 units left and 7 units down